Pemberdayaan Masyarakat Dan Keluarga Dalam Pencegahan Dan Penanganan Awal Ispa Pada Bayi Dan Balita Di Ampenan, Kota Mataram - Haryani, Haryani; Thoyibah, Zurriyatun; Hajri, Zuhratul; Hardiani, Sri; Arifn, Zaenal (Jurnal LENTERA, 2021)
Acute Respiratory Infection (ARI) is a health problem in developed and developing countries. This is due to the high morbidity and mortality rates due to ARI among children under five. ARI is included in the top 10 disease category in NTB with the highest number of visits, that is 174,213 (NTB Health Profile, 2020). In general, there are 3 risk factors for ARI,that is environmental factors, individual child factors and behavioral factors. Behavioral factors can be changed by increasing knowledge in the family. Observations in Karang Ujung Village show the lack of family knowledge about ARIs, how to prevent and treat them early. Therefore, it is important to conduct socialization through community and family empowerment activities in the prevention and early treatment of ARI in infants and toddlers in Karang Ujung Village. Activities are carried out in 3 stages, as follows: 1) identification of the number of infant and toddlers; 2) socialization, and 3) evaluation. The number of mothers with infant and toddlers who participated in community activities was 25 people. The results of the evaluation show that mothers of infants and toddlers have an understanding of ARI, how to prevent and early treat when a child has a cough. It is hoped that the people of Karang Ujung Village can immediately take preventive measures to prevent the occurrence of ARI in infants and toddlers and in the event of ARI disease in their families